BRAZILIAN MUNICIPALITIES: CHALLENGES OF FEDERALISM - Folha de Araújo Oliveira, Mirian (Revista Gênero e Interdisciplinaridade, 2024)
This article aims to address the issue of federalism and its consequences in conceptual terms allowing some historical setbacks that contributed to the construction of the current model in the country. The focus is on the municipality as a federated entity, the result of the promulgation of the 1988 Constitution and its consequences emphasizing the municipality as a federated entity and its current constitutional incumbers. In this reflection I intend to point and make reflections on weaknesses, challenges and achievements derived from the performance of this federative entity, with emphasis on the educational sector, when I present elements gathered from a survey of studies with the purpose of identifying political-institutional, economic and cultural factors that imply its performance.